Incorporating potable water sources and use habits into surveys that improve surrogate exposure estimates for water contaminants: the case of bisphenol A - Andra, Syam S.; Makris, Konstantinos C. (My University, 2014)
Human biomonitoring studies for water contaminants are often accompanied by surveys relying solely on total drinking water consumption rates, thus, failing to account for specific water sources (bottled and tap water) and use habits, such as water used for preparing cold/hot beverages (coffee, tea, juice, etc.). Despite the extensive use of bisphenol A (BPA) in polycarbonate (PC)-based water contact materials, rarely do BPA biomonitoring studies focus on various PC water uses and sources. Better resolved water consumption rates could reduce the uncertainty associated with surrogate daily BPA intake estimates using fine-tuned surveys. This approach provided a proof of concept on inclusion of water consumption from various sources and uses into estimates of daily intake for water contaminants like BPA found in water-contact materials. The next steps would be in quantifying the extent of improvement in exposure assessment that adds value to refined survey designs.
Keywords: Biomonitoring; Bisphenol A; Environmental epidemiology; Exposure assessment; Polycarbonate bottled water; Water and health